2020
DOI: 10.1155/2020/3679585
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glycerol and Sodium Pentaborate Formulation on Prevention of Postoperative Peritoneal Adhesion Formation

Abstract: Background. Postoperative peritoneal adhesions (PPA) are a serious problem for abdominal surgery. An effective remedy has not been found yet. New formulation of glycerol and sodium pentaborate may be able to solve the problem. Method. Female Wistar albino rats were randomly assigned into four equal groups. The adhesion model was created on the caecum anterior wall and covered with 2 ml 0.9% NaCl, 3% glycerol, 3% sodium pentaborate, and 3% glycerol plus 3% sodium pentaborate solutions in the groups, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…We produced new formulation compounded with 3% glycerol and 3% sodium pentaborate and patented it. We demonstrated that this new formulation reduces PPA more effectively than glycerol by itself 20 .…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…We produced new formulation compounded with 3% glycerol and 3% sodium pentaborate and patented it. We demonstrated that this new formulation reduces PPA more effectively than glycerol by itself 20 .…”
Section: Introductionmentioning
confidence: 79%
“…The wound healing effects of various boron compounds have previously been demonstrated 17 , 19 . During in-vitro and in-vivo studies performed by our team, sodium pentaborate was shown to exert anti-inflammatory effects through cell proliferation, cell migration, and growth factor expression pathways and to accelerate wound healing in different wound models 17 , 19 , 20 . In a prospective randomized clinical trial, we also showed that sodium pentaborate gel can prevent radiation-induced dermatitis in breast cancer patients 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation